Ankyrin-B in lens architecture and biomechanics: Just not tethering but more. Issue 2 (3rd March 2016) - Rao, Ponugoti Vasantha; Maddala, Rupalatha
ABSTRACT: The ankyrins are a family of well-characterized metazoan adaptor proteins that play a key role in linking various membrane-spanning proteins to the underlying spectrin-actin cytoskeleton; a mechanistic understanding of their role in tissue architecture and mechanics, however, remains elusive. Here we comment on a recent study demonstrating a key role for ankyrin-B in maintaining the hexagonal shape and radial alignment of ocular lens fiber cells by regulating the membrane organization of periaxin, dystrophins/dystroglycan, NrCAM and spectrin-actin network of proteins, and revealing that ankyrin-B deficiency impairs fiber cell shape and mechanical properties of the ocular lens. These observations indicate that ankyrin-B plays an important role in maintaining tissue cytoarchitecture, cell shape and biomechanical properties via engaging in key protein: protein interactions required for membrane anchoring and organization of the spectrin-actin skeleton, scaffolding proteins and cell adhesive proteins.